Pembentukan Nilai Kedisiplinan Siswa Melalui Kegiatan Apel Pagi Di Mas Sumbersari Kowang Semanding Tuban - Munip Hidayati; Luluk Iddah Masrufah; Alfianti Sumsurrohmah; Ninik Hidayati (Yayasan Al-Afif, 2026)
This study aims to analyze the role of morning assembly in shaping students' disciplinary character at MAS Sumbersari Kowang Semanding Tuban. This study used a descriptive qualitative approach, with students, teachers, and school officials directly involved in the morning assembly. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted inductively through reduction, presentation, and drawing conclusions. The results indicate that morning assembly is effective as a habit-building strategy for instilling the values ​​of discipline, punctuality, responsibility, and building spiritual and social discipline. This activity is supported by teacher role models, educational sanctions, and structured routines. Furthermore, this study identified inhibiting factors such as distance from students' homes, family support, and environmental conditions, demonstrating the need for synergy between schools, families, and the community. In conclusion, morning assembly is not simply a formal routine, but rather a strategic instrument capable of shaping students' disciplinary character comprehensively.